Commons vs. Commerce – managing water resources between pineapple production and nature conservation - Wilke, Dennis (2025)
Water is pivotal for the growth of pineapple plants throughout their life cycle. In Costa Rica’s rural areas, water is often provided as a common good by community-based water organizations (CWOs). Due to their reliance on locally available water resources, they are vulnerable to the water-related actions exerted by other users of their resource systems, such as water contamination through utilization of agrochemicals in pineapple production. In this article, we look more closely at the ongoing spatial fragmentation and the pressure for resource use through pineapple expansion in Costa Rica in the context of the Sustainable Development paradigm. We highlight the resulting consequences for common-pool resource (CPR) systems, exemplified by water contamination for CWOs in the northern Costa Rican canton of Río Cuarto. Drawing on insights from eight semi-structured interviews with different stakeholders, we analyze how the situation affects local CWOs, how these stakeholders address the consequences, and how they strive to improve the situation. We found that the situation accentuates power imbalances between CWOs and powerful private actors, jeopardizing the CWOs’ economic viability. However, their proposed long-term strategies may exacerbate water scarcity and resource conflicts. Instead, we argue that effective solutions would comprise regulatory instruments, accountability of the contaminators for their actions, as well as a stronger involvement of CWOs in decision making. Calls for a balanced development model that prioritizes community interests and environmental conservation over economic growth underscore the need for a paradigm shift in national policy frameworks.